Episteme des Pikaresken - Struwe, Carolin (De Gruyter, 2016)
Die Studie widmet sich den frühen deutschen pikaresken Texten des 17. Jahrhunderts (Albertinus'
10.1515/9783110429619
Keywords: German fiction / Early modern; 1500-1700 / History and criticism; Picaresque literature; German / History and criticism; Literatur / 17. Jahrhundert; Pikareske Literatur; LITERARY CRITICISM / European / German